2011
DOI: 10.1103/physrevb.83.155408
|View full text |Cite
|
Sign up to set email alerts
|

Zero field spin polarization in a two-dimensional paramagnetic resonant tunneling diode

Abstract: We study I-V characteristics of an all-II-VI semiconductor resonant tunneling diode with dilute magnetic impurities in the quantum well layer. Bound magnetic polaron states form in the vicinity of potential fluctuations at the well interface while tunneling electrons traverse these interface quantum dots. The resulting microscopic magnetic order lifts the degeneracy of the resonant tunneling states. Although there is no macroscopic magnetization, the resulting resonant tunneling current is highly spin polarize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In such a spin filter, 16 the change of the spin polarization of the current requires the change of the external magnetic field. In the recently fabricated paramagnetic resonant tunneling diodes (RTDs) [17][18][19] , the electrical control of the spin polarization of the current has been achieved. The spinpolarized current is controlled by the bias voltage in the presence of the external magnetic field in paramagnetic RTDs 17,18,20,21 or even without the external magnetic field in ferromagnetic RTDs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such a spin filter, 16 the change of the spin polarization of the current requires the change of the external magnetic field. In the recently fabricated paramagnetic resonant tunneling diodes (RTDs) [17][18][19] , the electrical control of the spin polarization of the current has been achieved. The spinpolarized current is controlled by the bias voltage in the presence of the external magnetic field in paramagnetic RTDs 17,18,20,21 or even without the external magnetic field in ferromagnetic RTDs.…”
Section: Introductionmentioning
confidence: 99%
“…In the recently fabricated paramagnetic resonant tunneling diodes (RTDs) [17][18][19] , the electrical control of the spin polarization of the current has been achieved. The spinpolarized current is controlled by the bias voltage in the presence of the external magnetic field in paramagnetic RTDs 17,18,20,21 or even without the external magnetic field in ferromagnetic RTDs. [22][23][24][25][26][27] If the quantum well in the RTD is made from the DMS, the spin splitting of the quasi-bound state energy level gives rise to the a To be published in Phys.Rev.B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resonant tunneling diodes (RTDs) have also been a research focus for many years [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Several works investigated their fundamental physical properties and possible potential applications in spintronics [8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Several works investigated their fundamental physical properties and possible potential applications in spintronics [8][9][10][11][12][13][14][15][16][17] . For example, it was shown that spin polarization of carriers in RTDs can be voltage and light dependent under magnetic field [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%